Sale of goods - Atiyah, P. S. (Pearson/Longman, 2005)
The new edition of 'The Sale of Goods' gives a full and detailed account of the English law of the sale of goods. It also includes a treatment of the law as it applies in Scotland and Northern Ireland. The 11th edition is brought right up to date with legislative and common law changes that have taken place over the past four years